CHEMICAL CHARACTERISTICS OF Sardinella lemuru HEAD MEAL AS A RAW MATERIAL FOR MAKING PROCESSED FOOD - Mutamimah, Dewi; Arista, Yuvita Lira Vesti (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2023)
Lemuru is one of the abundant marine food in Banyuwangi and is used as raw material for canned fish. The production of lemuru (Sardinella lemuru) catches reaches 160 tons in 2023 based on data obtained from UPT PPP Muncar. and produces about 30-40% of the total weight of fish waste, which is around 48-64 Tons which has not been utilized optimally.head of fish is one of waste and can use as material in making food products. This research aimed to determine the chemical characteristics of Sardinella lemuru head meal. The research method of chemical characteristics used was proximate analysis including moisture content by gravimetric method, protein conten by kjeldhal methodt, fat content by soxhlet method, ash content by dry ashing method and carbohydrate by different. The proximate content of lemuru head meal was 3,34% of moisture content, 19,76% of protein, 34,86% of fat, 17,85% of ash and 24,19% of carbohydrate content.